2017
DOI: 10.3346/jkms.2017.32.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Regarding HPV Vaccinations of Children among Mothers with Adolescent Daughters in Korea

Abstract: The aim of this study, carried out before the beginning of human papillomavirus (HPV) vaccinations as a National Immunization Program (NIP) in Korea in 2016, is to assess the ranges of perceptions and personal experience and their influences on attitudes regarding HPV vaccinations of children, among mothers of adolescent (9–14 years of age) daughters in Korea. From November 2015 to February 2016, we distributed a written questionnaire to mothers who had daughters aged 9–14 years. The questionnaire consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
0
27
2
3
Order By: Relevance
“…Women in Shenzhen were more willing to have their daughter(s) vaccinated than women in other cities in China and in developed countries . A multicentre survey in China had reported that mothers are more reluctant than fathers to accept vaccination for their children and that they are more suspicious of newly developed vaccines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in Shenzhen were more willing to have their daughter(s) vaccinated than women in other cities in China and in developed countries . A multicentre survey in China had reported that mothers are more reluctant than fathers to accept vaccination for their children and that they are more suspicious of newly developed vaccines .…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations might be that mothers would pay more attention to HPV vaccination if they had daughter(s), leading to a better understanding of HPV and its vaccine, which furthered the intention to have both themselves and their daughter (s) vaccinated. Women in Shenzhen were more willing to have their daughter(s) vaccinated than women in other cities in China [10,[29][30][31] and in developed countries [15,32]. A multicentre survey in China had reported that mothers are more reluctant than fathers to accept vaccination for their children and that they are more suspicious of newly developed vaccines [31].…”
Section: Discussionmentioning
confidence: 99%
“…33 The analysis of chi-square value was 4.4705 with the p=0.1069 which is not significant. 34 This reveals that there is no association between the level of knowledge and sex. Analysis of the participants according to their standard, majority of adolescent girls studying in 9 th standard (38.3%) and there are 18.3% of adolescent girls are studying in 8 th standard.…”
Section: Knowledge About Socio-demographic Variablesmentioning
confidence: 94%
“…36 Adverse events associated to the vaccine. 42 Knowledge about HPV. 39 Mothers' lack of knowledge about the vaccine, uncertainty about its safety or effectiveness, worries about future sex life and vaccine costs.…”
Section: Factors Associated To Hpv Vaccine Adherence Factors Associatmentioning
confidence: 99%